PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT QUANTUM TOSAN INTERNASIONAL - Samsul Ma’arif; Ida Nurlina (Al Hasanah Barokah Foundation, 2025)
This study aims to analyze the influence of motivation and work environment on employee performance at PT Quantum Tosan Internasional. This study is motivated by the importance of quality human resources in supporting company productivity, as well as the discovery of performance fluctuations and fairly high absenteeism rates in the company. The approach used is quantitative with a saturated sample method, involving the entire population of 61 respondents. Data collection techniques were carried out through questionnaires, while data analysis techniques used classical assumption tests, multiple linear regression analysis, t- tests and F-tests, and coefficients of determination. The results of the study indicate that motivation and work environment have a positive and significant effect on employee performance. This is evidenced by the regression equation Y = 6.615 + 0.034 X1 + 0.072 X2. The t-test shows that motivation (X1) has a significant influence on employee performance (Y) with a calculated t value > t table (5.655 > 1.671), and the work environment (X2) also shows a significant influence with a calculated t value > t table (6.007 > 1.671), both with significance <0.05. The F test states that simultaneously both independent variables have a significant effect on employee performance with F count 36.955 > F table 3.15 and significance 0.001 <0.05. This study concludes that increasing Motivation and improving the work environment need to be continuously done to increase employee performance productivity.